Middle East and North Africa Region Little Data Book, April 2012 - Mottaghi, Lili (World Bank, Washington, DC, 2014)
The data in this book are based on World Bank's World Development Indicators (WDI) 2011. The data are for 2009 and 2010 or the most recent year unless otherwise noted. Glossary contains definitions of the terms used in the tables.